Programmed cell death protein-1 (PD-1) protects liver damage by suppressing IFN-γ expression in T cells in infants and neonatal mice - Guo, Xuangjie; Xu, Yiping; Luo, Wei; Fang, Rongli; Cai, Li; Wang, Ping; Zhang, Yuxia; Wen, Zhe; Xu, Yanhui (BMC pediatrics, 2021)
Biliary atresia (BA) is a severe cholangiopathy possibly resulting from virus-induced and immune-mediated injury of the biliary system. IFN-γ, secreted from CD4 Th1 cells and CD8 cytotoxic T cells, is a major mediator of liver pathology. Programmed death protein-1 (PD-1) signaling suppresses T cell function. However, how PD-1 modify T cell function in BA remains incompletely understood. Frequencies of PD-1 expressing CD4 and CD8 T cells were analyzed in the liver and blood from BA and control subjects. Associations of PD-1 CD4 /CD8 T cell abundances with liver function indices were measured. Function of PD-1 was measured by administration of an anti-PD-1 antibody in a Rhesus Rotavirus (RRV)-induced BA model. Survival, histology, direct bilirubin, liver immune cell subsets and cytokine production were analyzed. PD-1 was significantly upregulated in CD4 and CD8 T cells in patients with BA compared with control subjects. PD-1 expression in T cells was negatively associated with IFN-γ concentration in liver (PD-1 CD4 T cells in liver vs. IFN-γ concentration, r = - 0.25, p = 0.05; PD-1 CD8 T cells in liver vs. IFN-γ concentration, r = - 0.39, p = 0.004). Blockade of PD-1 increased IFN-γ expression in CD4 T and CD8 T cells (RRV vs. anti-PD-1 treated RRV mice: 11.59 ± 3.43% vs. 21.26 ± 5.32% IFN-γ in hepatic CD4 T cells, p = 0.0003; 9.33 ± 4.03% vs. 22.55 ± 7.47% IFN-γ in hepatic CD8 T cells, p = 0.0001), suppressed bilirubin production (RRV vs. anti-PD-1 treated RRV mice: 285.4 ± 47.93 vs. 229.8 ± 45.86 μmol/L total bilirubin, p = 0.01) and exacerbated liver immunopathology. PD-1 plays a protective role in infants with BA by suppressing IFN-γ production in T cells. Increasing PD-1 signaling may serve as a therapeutic strategy for BA.